2013
DOI: 10.1002/wsbm.1253
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology‐embedded target validation: improving efficacy in drug discovery

Abstract: The pharmaceutical industry is faced with a range of challenges with the ever‐escalating costs of drug development and a drying out of drug pipelines. By harnessing advances in ‐omics technologies and moving away from the standard, reductionist model of drug discovery, there is significant potential to reduce costs and improve efficacy. Embedding systems biology approaches in drug discovery, which seek to investigate underlying molecular mechanisms of potential drug targets in a network context, will reduce at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…However, computational mathematical models are being generated to predict mode-of-action and responses-to-treatments (perturbations) not just at the molecular level but across all levels of biological organisation, including molecular, gene regulatory networks, signal transduction pathways and metabolic networks, cell populations, tissue level and whole organism models [10,[35][36][37][38]. In addition, models are being generated to account for pharmacokinetics and pharmacodynamics to analyse drug action, and even human-population level pharmacogenomics models of disease risk [10,39,40]. A direct challenge facing precision medicine is not only the generation of models at these disparate levels but the incorporation of models accounting for different levels of organisation into holistic multi-scale models [10] While not all treatment decisions require holistic multi-scale models, the aging demographic of the global population [45,46] is driving increased occurrence of comorbidities.…”
Section: Precision Medicine Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, computational mathematical models are being generated to predict mode-of-action and responses-to-treatments (perturbations) not just at the molecular level but across all levels of biological organisation, including molecular, gene regulatory networks, signal transduction pathways and metabolic networks, cell populations, tissue level and whole organism models [10,[35][36][37][38]. In addition, models are being generated to account for pharmacokinetics and pharmacodynamics to analyse drug action, and even human-population level pharmacogenomics models of disease risk [10,39,40]. A direct challenge facing precision medicine is not only the generation of models at these disparate levels but the incorporation of models accounting for different levels of organisation into holistic multi-scale models [10] While not all treatment decisions require holistic multi-scale models, the aging demographic of the global population [45,46] is driving increased occurrence of comorbidities.…”
Section: Precision Medicine Approachesmentioning
confidence: 99%
“…The development of computational models to enable researchers to map the functioning and malfunctioning of the human body, across multiple levels of structural and functional organisation, has been identified as central to the implementation of precision medicine by the CASyM Consortium [8]. In addition to patient stratification for personalised treatment, precision medicine approaches have the potential to assist in the design of multidrug treatments and repositioning of existing drugs [39]. Mechanistic understanding of disease should facilitate the in silico identification of drugs approved for treatment of one condition which would be beneficial for other previously unrelated conditions, by revealing common deregulated network features and vulnerable nodes/targets.…”
Section: Interpreting the Data Deluge At The Level Of The Individualmentioning
confidence: 99%
“…Additionally, a study of the phase III trials showed that two‐third of failed phase III trials between 2007 and 2010 were ascribed to low efficacy . Low drug efficacy is largely due to insufficient target validation at the preclinical stage . Therefore, reasonable target selection is an efficient strategy to mitigate risk in preclinical drug discovery .…”
Section: Introductionmentioning
confidence: 99%
“…Circles, triangles, and pentagons in different colors represent disease-related genes preclinical stage. 9 Therefore, reasonable target selection is an efficient strategy to mitigate risk in preclinical drug discovery. 10 Indeed, the identification of novel, promising drug targets with potentially high clinical efficacy is a critical step in the modern drug discovery pipeline, [9][10][11] but still remains a great challenge.…”
mentioning
confidence: 99%
“…One criticism of strict target-based approaches is that they may be too reductionist and may neglect other crucial components of the relevant biology 38,39 . Therefore, taking a more global biological systems-based approach and carefully defining the target pathway or pathways may also be important at this juncture.…”
Section: Mitigation Of Risk In Target Selectionmentioning
confidence: 99%